Kajian Studi Literatur Model Pembeajaran Discovery Learning untuk Meningkatkan Hasil Belajar Peserta Didik Pasca Pandemi Covid-19: Array - Rizki Kurniawan; Neviyarni; Herman Nirwana (eductum: Jurnal Literasi Pendidikan, 2022)
This study aims to determine the increase in learning outcomes through the Discovery Learning learning model as a learning innovation that can be applied by educators after the Covid-19 pandemic. Through a literature review, the "library research" method of literature analysis was used in this study to complete the analysis of the various sources used. Formulation of research questions at the beginning of the study followed by examining research findings related to E-journal non-test tracking using indexed journal articles, books, theses, and online articles related to the application of Discovery Learning to collect data for this literature review. After the Covid-19 pandemic that occurred in Indonesia, the results of a literature study showed that the application of learning and teaching strategies using the Discovery Learning model was quite successful in order to improve student learning outcomes after the Covid-19 pandemic. From the literature studies that have been carried out, it is revealed that Discovery Learning as a post-Covid-19 learning model contributes to increasing the final results of the learning and teaching process of students.